Association between NR3C1 gene polymorphisms and age-related hearing impairment in Qingdao Chinese elderly - Wanxue Song; Hainan Cao; Dongfeng Zhang; Haiyan Xu; Qianqian Zhang; Zhaoguo Wang; Suyun Li; Weijing Wang; Wenchao Hu; Bingling Wang; Haiping Duan (BMC, 2021)
Abstract Background Age-related hearing impairment (ARHI) has attracted increasing attention recently. It is caused by genetic and environmental factors. A number of ARHI-related genes have been found. This study aimed to detect the potential association between NR3C1 gene polymorphisms and ARHI by means of weighted allele score. Methods A total of 861 participants from Qingdao city were selected by means of cluster random sampling. We statistically evaluated the characteristics of individuals and used the Mann-Whitney U test or chi-square test for comparison. The publicly available expression quantitative trait locus (eQTL) was queried on the website of the Genotype-Tissue Expression (GTEx). We used the weighted allele score and logistic regression analysis to explore the association between NR3C1 gene polymorphisms and ARHI. Finally, the prediction model was constructed by logistic regression and receiver operating characteristic (ROC) curve. Results All individuals over 60 years of age were enrolled in this study. The allele of rs61757411, rs41423247 and rs6877893 were significantly different between the ARHI group and the normal hearing group (P < 0.01). Though eQTL analysis, rs6877893 and rs33388 might affect the occurrence of ARHI by affecting the expression of NR3C1 gene in artery aorta. Then we performed two models: one without adding any covariates into model and the other adjusting for demographic characteristic, smoking and drinking, diet and exercise, and physical conditions. In the multivariate-adjusted model 2, the odds ratio with 95% confidence interval for weighted allele score (NR3C1) was 0.841 (0.710-0.995, P = 0.043). The area under the ROC curve was 0.755, indicating that the model had good predictability. Conclusions Our study suggests that NR3C1 gene polymorphisms was significantly associated with ARHI.